Bioremediation of diesel and lubricant oil-contaminated soils using enhanced landfarming system. (December 2016) - Wang, Sih-Yu; Kuo, Yu-Chia; Hong, Andy; Chang, Yu-Min; Kao, Chih-Ming
Abstract: Lubricant and diesel oil-polluted sites are difficult to remediate because they have less volatile and biodegradable characteristics. The goal of this research was to evaluate the potential of applying an enhanced landfarming to bioremediate soils polluted by lubricant and diesel. Microcosm study was performed to evaluate the optimal treatment conditions with the addition of different additives (nutrients, addition of activated sludge from oil-refining wastewater facility, compost, TPH-degrading bacteria, and fern chips) to enhance total petroleum hydrocarbon (TPH) removal. To simulate the aerobic landfarming biosystem, air in the microcosm headspace was replaced once a week. Results demonstrate that the additives of activated sludge and compost could result in the increase in soil microbial populations and raise TPH degradation efficiency (up to 83% of TPH removal with 175 days of incubation) with initial (TPH = 4100 mg/kg). The first-order TPH degradation rate reached 0.01 1/d in microcosms with additive of activated sludge (mass ratio of soil to inocula = 50:1). The soil microbial communities were determined by nucleotide sequence analyses and 16S rRNA-based denatured gradient gel electrophoresis. Thirty-four specific TPH-degrading bacteria were detected in microcosm soils. Chromatograph analyses demonstrate that resolved peaks were more biodegradable than unresolved complex mixture. Results indicate that more aggressive remedial measures are required to enhance the TPH biodegradation, which included the increase of (1) microbial population or TPH-degrading bacteria, (2) biodegradable carbon sources, (3) nutrient content, and (4) soil permeability. Highlights: Enhanced landfarming was developed using unique operation and amendments. Enhanced landfarming could remediate lubricant and diesel contaminated soils effectively. Fern chips, compost, sludge could be applied to enhance TPH biodegradation efficiency. Chromatograph analysis is a useful indicator of the effectiveness of TPH biodegradation.